Red, blue, and purple America : the future of election demographics - Teixeira, Ruy A. (Brookings Institution Press, 2008)
"Analyzes changing patterns of immigration, settlement, demography, family structure, and religion, describing trends and their impacts on 2008 politics and beyond. Lays out implications for public policy and shows how these trends have shaped the Red and Blue divisions and might break apart those blocs in new and surprising ways"--Provided by publisher